2021
DOI: 10.1002/ppp3.10189
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and predicting forest degradation: A comparison of ground surveys and remote sensing in Tanzanian forests

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
(111 reference statements)
0
29
0
Order By: Relevance
“…Throughfall deposition does not fully reflect the total (wet + dry) atmospheric deposition, however, because some substances are taken up or excreted or leached by tree canopy. In this paper we do not attempt to evaluate the effect of canopy interaction on throughfall deposition, discussed for example by Draaijers and Erisman (1995), Staelens et al (2008), Talkner et al (2010), or Ahrends et al (2021). Sites of the Swedish SWETHRO Network (Pihl- Karlsson et al, 2011) are not formally a part of ICP Forests, but the data are reported to ICP Forests, and used in this study.…”
Section: Icp Forests and Swethro Deposition Measurementsmentioning
confidence: 99%
“…Throughfall deposition does not fully reflect the total (wet + dry) atmospheric deposition, however, because some substances are taken up or excreted or leached by tree canopy. In this paper we do not attempt to evaluate the effect of canopy interaction on throughfall deposition, discussed for example by Draaijers and Erisman (1995), Staelens et al (2008), Talkner et al (2010), or Ahrends et al (2021). Sites of the Swedish SWETHRO Network (Pihl- Karlsson et al, 2011) are not formally a part of ICP Forests, but the data are reported to ICP Forests, and used in this study.…”
Section: Icp Forests and Swethro Deposition Measurementsmentioning
confidence: 99%
“…The removal of the blocks operates such as gradual changes making the structure unstable (low resilience) until the wooden block collapse (irreversible state). Similarly, tipping points theory behave in the same way, with each day of accumulated environmental stress pushing the ecosystem closer to irreversible state such as desertification [43].…”
Section: Drought Drive To Land Degradation As the Major Impact On Ter...mentioning
confidence: 96%
“…As it mentioned before, the low resilience of an ecosystem faced critical transitions before is close to a tipping point due to the low trend of its recovery. The three metrics that depict an upcoming critical transition in any dynamic system such as an ecosystem are the spatial variance / standard deviation, skewness and autocorrelation [43]. The estimation trend of the above metric-based indicators implemented through Kendall's τ.…”
Section: Application Of Early-warning Signals On Vegetation Changesmentioning
confidence: 99%
“…First experiences to identify individual tree species confirmed the high value of RSD, thanks to the increasing availability of higher-resolution images at high frequency [28,87,88]. Parallel efforts to generate ground data [50] provide fundamental knowledge to get better accuracy on RSD-based maps [22]. As RSD classification maps are assessed by "ground-truthing" [55], obtaining accurate field data is key to getting accurate species distribution maps.…”
Section: The Use Of Remote Sensing Data To Validate Species Distribution Modelsmentioning
confidence: 99%
“…Satellite spectral information (RSD) in combination with attributes obtained from inventory plots is a growing research field to investigate ecosystem functioning and to detect plant assemblages or ecosystem properties' changes in time that complement in situ terrestrial monitoring approaches [22,23]. Multi-spectral biophysical estimates of vegetation have been used to map large areas of forests [24] or to assist forest surveys for stratification and post-stratification field sampling [25].…”
Section: Introductionmentioning
confidence: 99%